A bibliometric analysis of Mediterranean diet on cancer from 2012 to 2021 - Liu, Yafeng; Lu, Jibin (Frontiers in Nutrition, 2023)
Background Numerous studies have demonstrated the value of the Mediterranean diet (MD) as a nutritious eating regimen for lowering the risk of cancer. This study aims to discuss the research patterns, existing state, and possible hotspots in implementing the MD for the prevention and treatment of cancer using bibliometrics. Methods The Web of Science Core Collection (WoSCC) was searched for articles on cancer that were related to the MD. CiteSpace, VOSviewer, Microsoft Excel 2019, and R software were utilized for bibliometric analysis and data visualization. Results There were 1,415 articles and reviews published from 2012 to 2021. Annual publication volume showed a continuous upward trend. Italy and Harvard University were the country and institution, respectively, with the highest number of publications on this topic. Nutrients ranked first in the number of documents, number of citations, and the H-index. James R. Hebert was the most productive writer, and Antonia Trichopoulou was the most co-cited author. “Alcohol consumption,” “oleic acid,” and “low density lipoprotein” were keywords used in earlier publications, while more recent hotspots focused on “gut microbiota,” “older adult,” and “polyphenol.” Conclusion Over the past decade, research on the MD in the field of cancer has received increasing attention. To improve the level of evidence for the beneficial effects of the MD on a range of cancers, more research on molecular mechanisms and better clinical studies are required.